A self-supported hierarchic 3D double skeleton host for highly stable lithium metal batteries. (April 2023) - Chen, Dongping; Qing, Piao; Tang, Fengcheng; Yu, Huaming; He, Pan; Huang, Haifeng; Wu, Zhibin; Sun, Fu; Wei, Weifeng; Ji, Xiaobo; Chen, Libao
Abstract: Lithium (Li) is identified as the most promising anode material for Li metal batteries but suffers from uncontrolled Li dendrites and infinite volume changes during repeated cycles. Herein, a unique self-supported hierarchic 3D Li–B–Zn composite framework with abundant lithophilic sites and outstanding structural stability is reported to address the mentioned challenges. The evenly distributed μm-sized LiZn rods act as mixed ion/electron conductors, facilitating accelerated Li + ions transport dynamics. Additionally, these μm-sized LiZn rods are intertwined with the nm-sized LiB fibers, forming a unique hierarchic 3D framework with enhanced overall structural integrity. Moreover, this unique 3D framework also provides sufficient interior space to accommodate the volume changes during repeated Li dissolution and deposition. These synergistic features decrease the likelihood of Li dendrites growth and suppress the volume change during battery cycling, which is confirmed by various experimental characterizations. The electrochemical performance of both the Li–B–Zn symmetrical cells and the Li–B–Zn|LiFePO4 full cells exhibit long-term cyclability, superior rate performance, and high Coulomb efficiency. The reported design of a unique self-supported hierarchic 3D Li–B–Zn composite skeleton opens up new opportunities for developing next-generation Li-based anode materials. Graphical abstract: Image 1 Highlights: A unique self-supported hierarchic 3D framework containing LiB–LiZn double skeletons is prepared in situ by melting method. The μm-sized LiZn rods are interwoven with the nm-sized LiB fibers to enhance the skeleton mechanical strength. The uniformly distributed LiZn rods possess enhanced lithiophilicity and improved Li +  ions transport kinetics. This unique hierarchic 3D framework can decrease the local current density and suppress volume changes during cycling. Due to the synergistic effects, the Li–B–Zn composite anode exhibits dendrites-free Li deposition and excellent performance.